Splenic arterial neurovascular bundle stimulation in esophagectomy: A feasibility and safety prospective cohort study - Brinkman, David J.; Gupta, Isha; Matteucci, Paul B.; Ouchouche, Sebastien; de Jonge, Wouter J.; Coatney, Robert W.; Salam, Tariqus; Chew, Daniel J.; Irwin, Eric; Yazicioglu, R. Firat; Nieuwenhuizen, Grard A. P.; Vervoordeldonk, Margriet J.; et al. (Frontiers in Neuroscience, 2022)
Introduction The autonomic nervous system is a key regulator of inflammation. Electrical stimulation of the vagus nerve has been shown to have some preclinical efficacy. However, only a few clinical studies have been reported to treat inflammatory diseases. The present study evaluates, for the first time, neuromodulation of the splenic arterial neurovascular bundle (SpA NVB) in patients undergoing minimally invasive esophagectomy (MIE), in which the SpA NVB is exposed as part of the procedure. Methods This single-center, single-arm study enrolled 13 patients undergoing MIE. During the abdominal phase of the MIE, a novel cuff was placed around the SpA NVB, and stimulation was applied. The primary endpoint was the feasibility and safety of cuff application and removal. A secondary endpoint included the impact of stimulation on SpA blood flow changes during the stimulation, and an exploratory point was C-reactive protein (CRP) levels on postoperative day (POD) 2 and 3. Results All patients successfully underwent placement, stimulation, and removal of the cuff on the SpA NVB with no adverse events related to the investigational procedure. Stimulation was associated with an overall reduction in splenic arterial blood flow but not with changes in blood pressure or heart rate. When compared to historic Propensity Score Matched (PSM) controls, CRP levels on POD2 (124 vs. 197 mg/ml, p = 0.032) and POD3 (151 vs. 221 mg/ml, p = 0.033) were lower in patients receiving stimulation. Conclusion This first-in-human study demonstrated for the first time that applying a cuff around the SpA NVB and subsequent stimulation is safe, feasible, and may have an effect on the postoperative inflammatory response following MIE. These findings suggest that SpA NVB stimulation may offer a new method for immunomodulatory therapy in acute or chronic inflammatory conditions.